2012
DOI: 10.1097/coc.0b013e31821dedf7
|View full text |Cite
|
Sign up to set email alerts
|

Chicken Skin Mucosa Surrounding Adult Colorectal Adenomas is a Risk Factor for Carcinogenesis

Abstract: The biological characteristics of colorectal adenomas with CSM were different from those of colorectal adenomas without CSM. Colorectal adenomas with CSM exhibited active cell proliferation and inhibition of apoptotic pathways, suggesting an increased risk of carcinogenesis in these adenomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Previous data indicated that adenocarcinomas and colorectal adenomas with CSM expressed similar levels of Ki-67 and COX-2 proteins; survivin and caspase-3, key regulators of apoptosis, were suppressed in colorectal adenomas with CSM. 12 Although these findings have important implications that the occurrence of colorectal cancer is associated with apoptosis, the sample size of the study was small and the clinical characteristics of the CSM patients were poorly characterized. It is uncertain whether CSM surrounding adult colorectal adenoma is a risk factor for colon carcinogenesis.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous data indicated that adenocarcinomas and colorectal adenomas with CSM expressed similar levels of Ki-67 and COX-2 proteins; survivin and caspase-3, key regulators of apoptosis, were suppressed in colorectal adenomas with CSM. 12 Although these findings have important implications that the occurrence of colorectal cancer is associated with apoptosis, the sample size of the study was small and the clinical characteristics of the CSM patients were poorly characterized. It is uncertain whether CSM surrounding adult colorectal adenoma is a risk factor for colon carcinogenesis.…”
Section: Discussionmentioning
confidence: 98%
“… 10 However, a recent study showed that colorectal neoplasm with CSM was associated with increased risk of carcinogenesis. 12 Colorectal adenomas with CSM in adults demonstrated higher Ki-67 and COX-2 expression as markers of cell proliferation and lower caspase-3 expression as a marker of apoptosis compared to colorectal adenoma without CSM. 12 In addition, the prevalence of CSM was higher in carcinoma patients (64.3%) than in adenoma patients (22.1%).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…CSM-related adenoma was mainly found in the distal colon (93.3%). Adenomas with CSM, compared to those without CSM, presented more high-grade dysplasia and carcinoma, higher expression of Ki-67, COX2 protein and survivin, and lower expression of caspase-3, which indicated the carcinogenetic progression of colorectal adenomas 28,29 . Hence, CSM is generally considered a tumor marker in colorectal adenomas.…”
Section: Discussionmentioning
confidence: 96%
“…Histopathologically, it represents fat accumulation in macrophages within the muscularis propria and, rarely, intestine-like microvilli. In two studies[31,32], the prevalence of chicken-skin-like mucosa was higher in carcinoma patients than in adenoma patients, and its role as a potential predictive marker of carcinogenetic progression was taken into consideration. However, it is a colonoscopic sign to search for a polyp in challenging locations.…”
Section: Factors Predicting Lymph Node Status In Malignant Pedunculatmentioning
confidence: 99%